NEED OF THE CHOICE OF LANGUAGE AND PLANNING OF A LESSON BY THE TEACHER AT ENGLISH LESSON (International relations and international law Journal, 2016)
The author in article proves a need of the choice of language and planning of a lesson by the teacher at English lesson.
Keywords: choice of language; planning of a lesson